الضغط المدرسي وعلاقته بالدافعية للتعلم دراسة ميدانية على عينة من تلاميذ السنة الثانية ثانوي بثانوية بوجمعة قرمة غرداية (مجلة الواحات للبحوث والدراسات, 2021)
The Study Aimed At Uncovering The Relationship Between The Pressure Of School And The Motivation To Learn. The Study Was Shortened To A Sample Of Students From The Second Year Of Secondary School Boudjemaa Qarma, Ghardaia. The Study Sample Consisted Of 71 Students And Students Who Were Chosen In A Deliberate Intentional Manner. 19.0) Spss, Correlation Coefficient Pearson, The Equation Of The Difference Between The Correlation Coefficients Of The Sex Variable Where The Results Reached The Following:-There Is No Relationship Between The Pressure Of School And Motivation To Learn For Students In The Second Year Secondary High School In Boudjemaa Qarma. -The Level Of School Pressure Among Second-Year Secondary Students At The High School In Boudjemaa Qarma Is High.-The Level Of Motivation For Learning Among Second Year Secondary Students At The High School In Boudjemaa Qarma Is High.-The Relationship Between School Pressure And Motivation Among Second Year Secondary School Students Differs Sex In Boudjemaa Qarma. Keywords- School Pressure - Motivation To Learn - Second Secondary Students.